Battle of the Teton Basin [large type] - Manning, Jason (Manning, Jason. High country, 2022)
"All Zach Hannah wants is to be left alone, high in the mountains with his bride, Morning Sky. But as long as Sean Devlin is alive, Zach will find no peace. Now Zach has to track down this man, the former friend who stole his wife and left him to die at the hands of his mortal enemies, the Blackfoot Indians. It's an odyssey that will lead him along the Santa Fe Trail and back to the high country, where the mountains echo with gunfire. As mountain men and Blackfoot braves clash in a struggle that will change the course of the American West, Zach and Devlin square off in a final reckoning that only one of them will survive."--Back cover